2020
DOI: 10.1080/20008686.2020.1754538
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a COVID-19 IgM and IgG rapid test; an efficient tool for assessment of past exposure to SARS-CoV-2

Abstract: COVID-19 is the most rapidly growing pandemic in modern time, and the need for serological testing is most urgent. Although the diagnostics of acute patients by RT-PCR is both efficient and specific, we are also crucially in need of serological tools for investigating antibody responses and assessing individual and potential herd immunity. We evaluated a commercially available test developed for rapid (within 15 minutes) detection of SARS-CoV-2-specific IgM and IgG by 29 PCR-confirmed COVID-19 cases and 124 ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
180
4
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(202 citation statements)
references
References 21 publications
9
180
4
9
Order By: Relevance
“…On the other hand, the sensitivity of the tested LFIA showed high variability between manufacturers compared to either RT-PCR or ELISA, although their speci city seems to be high upon testing serum obtained from healthy subjects. Importantly, very low sensitivity and higher variability were seen during early time points post symptoms onset as expected, consistent with the often delayed seroconversion in COVID-19 patients which could be delayed to day 11 to day 19 post symptoms onset (Hoffman et al, 2020). Similarly, we observed that antibody responses could peak around this time range, in which our ELISA results detected the initial increase of antibodies post day 7 of symptoms onset and peaking at day 11.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, the sensitivity of the tested LFIA showed high variability between manufacturers compared to either RT-PCR or ELISA, although their speci city seems to be high upon testing serum obtained from healthy subjects. Importantly, very low sensitivity and higher variability were seen during early time points post symptoms onset as expected, consistent with the often delayed seroconversion in COVID-19 patients which could be delayed to day 11 to day 19 post symptoms onset (Hoffman et al, 2020). Similarly, we observed that antibody responses could peak around this time range, in which our ELISA results detected the initial increase of antibodies post day 7 of symptoms onset and peaking at day 11.…”
Section: Discussionsupporting
confidence: 87%
“…In total, 4696 records based on screening of titles or abstracts and 235 after full text review were excluded. Forty studies totalling 73 study arms15161718192021222324252627282930313233343536373839404142434445464748495051525354 met the inclusion criteria. Table 1 summarises the studies by test method; the sum of the number of studies exceeds 40 because some evaluated more than one method.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarises the studies by test method; the sum of the number of studies exceeds 40 because some evaluated more than one method. Seventy per cent (28/40) of the studies were from China,16171819202122232425262728293031323334353839404145464748 8% (3/40) from Italy,153643 and the remainder from the United States (3/40),425052 Denmark (1/40),51 Spain (1/40),37 Sweden (1/40),53 Japan (1/40),44 the United Kingdom (1/40),49 and Germany (1/40) 5433…”
Section: Resultsmentioning
confidence: 99%
“…That means when the viral charge is high IgG/IgM tests reach high sensitivities and specificities. But 35 in that cases the disease is in advanced levels (Guo et al, 2020a;Hoffman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%